Exploring lean culture challenges in a small family-owned manufacturing company: a case study from Norway. (2016) - Pedersen-Rise, Oddbjørn; Haddud, Abubaker
The purpose of this study was to identify the differences between a family-owned small business culture and the lean manufacturing organisational culture. The study explored the potential challenges that will face the company if lean manufacturing is to be introduced and identified what the company should change to ensure its successful implementation. A single-case study utilising a 31-item questionnaire was used to collect the primary data. All the participants were current full-time employees of the selected company. The results revealed that family-owned small manufacturing businesses are influenced by the values and beliefs of their founders and owners; thus, implementing lean manufacturing will need a substantial organisational culture change. Another key finding was that, because such organisations are mainly influenced by their founders and owners, any potential cultural change fitting lean transformation should be prioritised. This study contributed to describing a common situation that many family-owned firms will recognise and highlighted important factors that are necessary to make a successful transformation to lean manufacturing. This study was limited to small family-owned manufacturing companies working in Norway and explored the cultural element of lean manufacturing only.